Linking of Repeated Games. When Does It Lead to More Cooperation and Pareto Improvements? - Pierre von Mouche; Henk Folmer (Fondazione Eni Enrico Mattei (FEEM), 2007)
Linking of repeated games and exchange of concessions in fields of relative strength may lead to more cooperation and to Pareto improvements relative to the situation where each game is played separately. In this paper we formalize these statements, provide some general results concerning the conditions for more cooperation and Pareto improvements to materialize or not and analyze the relation between both. Special attention is paid to the role of asymmetries.
Keywords: C72; 330; Environmental Policy; Linking; Folk Theorem; Tensor Game; Prsioners' Dilemma; Full Cooperation; Pareto Efficiency; Minkowski Sum; Vector Maximum; Convex Analysis; Wiederholte Spiele; Umweltpolitik; Folk-Theorem; Gefangenendilemma; Pareto-Optimum; Theorie